Developing a Collaborative Agenda for Humanities and Social Scientific Research on Laboratory Animal Science and Welfare. - Gail F Davies; Beth J Greenhough; Pru Hobson-West; Robert G W Kirk; Ken Applebee; Laura C Bellingan; Manuel Berdoy; Henry Buller; Helen J Cassaday; Keith Davies; Daniela Diefenbacher; Tone Druglitrø; et al. (PLoS ONE)
Improving laboratory animal science and welfare requires both new scientific research and insights from research in the humanities and social sciences. Whilst scientific research provides evidence to replace, reduce and refine procedures involving laboratory animals (the '3Rs'), work in the humanities and social sciences can help understand the social, economic and cultural processes that enhance or impede humane ways of knowing and working with laboratory animals. However, communication across these disciplinary perspectives is currently limited, and they design research programmes, generate results, engage users, and seek to influence policy in different ways. To facilitate dialogue and future research at this interface, we convened an interdisciplinary group of 45 life scientists, social scientists, humanities scholars, non-governmental organisations and policy-makers to generate a collaborative research agenda. This drew on methods employed by other agenda-setting exercises in science policy, using a collaborative and deliberative approach for the identification of research priorities. Participants were recruited from across the community, invited to submit research questions and vote on their priorities. They then met at an interactive workshop in the UK, discussed all 136 questions submitted, and collectively defined the 30 most important issues for the group. The output is a collaborative future agenda for research in the humanities and social sciences on laboratory animal science and welfare. The questions indicate a demand for new research in the humanities and social sciences to inform emerging discussions and priorities on the governance and practice of laboratory animal research, including on issues around: international harmonisation, openness and public engagement, 'cultures of care', harm-benefit analysis and the future of the 3Rs. The process outlined below underlines the value of interdisciplinary exchange for improving communication across different research cultures and identifies ways of enhancing the effectiveness of future research at the interface between the humanities, social sciences, science and science policy.